1987
DOI: 10.1037/0022-006x.55.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Social competence and parental support as mediators of the link between stress and metabolic control in adolescents with insulin-dependent diabetes mellitus.

Abstract: This study investigated whether the link between stress and metabolic control in adolescents with insulin-dependent diabetes mellitus (IDDM) is direct or indirect and whether this association is mediated by either social competence or parental support. Subjects included 104 adolescents with IDDM and their mothers. Measures of adherence, life stress, social competence, and parental support were obtained during the assessment session, and metabolic control was determined by averaging the adolescent's glycosylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
108
3
4

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 29 publications
10
108
3
4
Order By: Relevance
“…3,9,12 To summarize these studies' findings: • Higher family cohesion, parental warmth (defined as support and affection), and an "authoritative" style of parenting (which involves being engaged with the child with warmth while limit-setting and having high maturity demands with low levels of coercive control) are related to higher levels of adherence and cooperation by the child or adolescent with the tasks of diabetes treatment and to better glycemic control. • Higher general family conflict, parental restrictiveness, and criticism and an "authoritarian" style of parenting (high levels of maturity demands with high levels of coercive control) are related to lower levels of adherence and cooperation by the child or adolescent with the tasks of diabetes management and to poorer glycemic control.…”
Section: In Briefmentioning
confidence: 99%
See 1 more Smart Citation
“…3,9,12 To summarize these studies' findings: • Higher family cohesion, parental warmth (defined as support and affection), and an "authoritative" style of parenting (which involves being engaged with the child with warmth while limit-setting and having high maturity demands with low levels of coercive control) are related to higher levels of adherence and cooperation by the child or adolescent with the tasks of diabetes treatment and to better glycemic control. • Higher general family conflict, parental restrictiveness, and criticism and an "authoritarian" style of parenting (high levels of maturity demands with high levels of coercive control) are related to lower levels of adherence and cooperation by the child or adolescent with the tasks of diabetes management and to poorer glycemic control.…”
Section: In Briefmentioning
confidence: 99%
“…1 Moreover, it is well documented that higher levels of conflict in the family correlate with lower levels of child adherence to the diabetes treatment regimen. [2][3][4][5][6][7][8] General family conflict has been demonstrated to relate to adherence in youth with type 1 diabetes in both cross-sectional studies 3,4,8 and longitudinal, prospective research. 9 In a study of parenting, child development, and diabetes adherence and control, Miller-Johnson et al 10 demonstrated that ratings of increased conflict were directly related to diabetes adherence problems and poorer blood glucose control.…”
Section: Recent Research On General Conflict and Parenting Behavior Imentioning
confidence: 99%
“…17 In adolescents with or at risk for diabetes, social competence has been associated with better emotional well-being, 15 better ability to manage stress, and better metabolic control. 18,19 Coping is a complex process that can be defined as "constantly chang-ing cognitive and behavioral efforts to manage specific external and/or internal demands that are appraised as taxing or exceeding the resources of the person." 20 According to Lazarus and Folkman, 20 the first step in coping is cognitive appraisal, which is crucial to the impact of a particular disease on a particular child.…”
Section: Coping Skills Training For Youths With Diabetesmentioning
confidence: 99%
“…This developmental task may be more complicated for adolescents with type 1 diabetes because, at this time in their lives, both metabolic control and treatment adherence often deteriorate [7][8][9][10][11][12][13][14], and less parental involvement in diabetes care has been associated with poorer diabetes outcomes [8,15]. In contrast, adolescents whose parents remain involved in self-care activities show better adherence and more effective glycemic control [7,16].…”
mentioning
confidence: 99%